HIGH-PRECISION FOLLOW-UP OBSERVATIONS OF NEAR-EARTH OBJECTS - Maigurova, N. V.; Pomazan, A. V.; Shulga, A. V. (Одеські астрономічні публікації, 2018)
Main objective of the study is orbit refinement of Near-Earth Objects (NEOs) as part of the global task of asteroid-cometary hazard. We present the latest results of ongoing high-precision astrometric follow-up observations of NEOs using the Mykolaiv Observatory KT-50 telescope of Mobitel Complex that equipped Alta U9000 CCD camera. Main feature of the objects of this study is the fast moving in the field of view. That circumstance makes impossible to observe NEOs as point images and to obtain their precise coordinates by the classical methods of observation. We used modified Rotating-drift-scan CCD mode for obtaining NEOs images and classical mode – for obtaining fields with reference stars to carry out astrometric reductions. The combination of classical and modified observational modes allows us to recover objects having V < 17 with high astrometric precision. The comparative statistics of Mykolaiv observations of NEOs for the period 2015-2018 and analysis of positional accuracy are presented. The results of the effect of new observational data on the residual differences (O-C) in both coordinates with respect to HORIZONS JPL ephemerides are shown on examples two potentially-hazard asteroids (2001KB67 and 2017YE5) during their close approaching to Earth in 2018. It is shown that adding new observations can significantly improve the accuracy of determining the orbital elements of such objects. CCD observations; asteroid-cometary hazard; near-earth asteroids; potentially hazard asteroids; ephemerids of small Solar system bodies